Ellis's model of student information-seeking behavior on Google Scholar - Prijana, Prijana; Abdussalam, Razif; Pancasona, Raka Gading; Sulaiman, Kabir Alabi (Universitas Padjadjaran, 2023)
Information seeking leads to interactions within a system. At the same time, interaction patterns can potentially lead to a behavioral tendency and form a unique behavioral pattern. This research aimed to find out how information search behavior was carried out by students of the Library and Information Science Study Program in conducting literature searches on the Google Scholar platform by applying the stages of the Ellis Model. The research method used quantitative with a survey method. The results showed that at the starting stage, the correlation coefficient was moderate; at the chaining stage, the correlation coefficient was moderate; at the browsing stage, the correlation coefficient was below moderate; at the monitoring stage, the correlation coefficient was below moderate; at the differentiating stage, the correlation coefficient was moderate; and at the extracting stage, the correlation coefficient was below moderate. This study concludes that students know the topic they want to search before using Google Scholar. Chaining, browsing, and monitoring are done alternately at almost the same time. Students have observed the correlation coefficient numbers at the chaining, browsing, and monitoring stages; students pay more attention to the chaining stage, namely obtaining keywords. At the differentiating stage, students have begun to filter incoming information and use their ability to distinguish the sources of information obtained, and at the extracting stage, students work through the selected sources to identify all relevant materials.